Anti-friction and anti-wear titanium alloy for bearing and preparation method thereof

By forming Ti3ALC2, MO2ALC2, and TI3AL nano -phase with self -lubrication function on the surface of the titanium alloy, the problem of lack of lubrication conditions in high temperature environments in high temperature environments has been solved. And lubricating effect.

CN119372745APending Publication Date: 2025-01-28HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411482449.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing titanium alloy sliding bearings are prone to lack of lubrication conditions under high temperature environments, resulting in the friction pair being in a boundary friction or dry friction state, increasing wear and limiting their service life.

Method used

Through the titanium aluminum aluminum composite coating of nano-tic and MO2C particles on the surface of the titanium alloy, and use high-energy femtosecond laser beams to induce Ti-Al-C, MO-AL-C, Ti-Al in situ Ti3ALC2, MO2ALC2, and Ti3AL nano -phase structure with lubrication function.

Benefits of technology

It significantly reduces the wear rate of titanium alloy sliding bearing, and improves its abrasion resistance and lubrication, and is suitable for wider temperature areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372745A_ABST
    Figure CN119372745A_ABST
Patent Text Reader

Abstract

The invention discloses an antifriction and antiwear titanium alloy for a bearing and a preparation method of the antifriction and antiwear titanium alloy. Comprising a substrate, and the surface of the substrate is loaded with Ti3AlC2, Mo2AlC2 and Ti3Al nanophase which is formed through in-situ reaction and has a self-lubricating function. Nano TiC and Mo2C particles are dispersed in electrolyte containing AlCl3 and TiCl4, the TiC and Mo2C loaded Ti-Al composite coating is electrodeposited on the surface of a base body by adopting an ionic liquid mixing electrodeposition process, sweeping is conducted on the surface of the composite coating by means of a high-energy femtosecond laser beam, in-situ reaction among Ti-Al-C, Mo-Al-C and Ti-Al is induced at high temperature, and the composite coating is prepared. And then a micropore structure loaded with in-situ nanometer self-lubricating Ti3AlC2, Mo2AlC2 and Ti3Al particles is formed on the surface of the coating. According to the anti-friction and anti-wear titanium alloy for the bearing and the preparation method of the anti-friction and anti-wear titanium alloy, the effects of high wear resistance and high lubricity can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a titanium alloy, in particular to a friction-reducing and wear-resistant titanium alloy for bearings and a method for preparing the same. Background Art

[0002] With the continuous development of light alloys, titanium alloys with high load-bearing capacity, light weight, low friction coefficient and excellent anti-seizure performance have become one of the ideal materials for the manufacture of sliding bearing alloys, which can replace traditional spherical bearing materials such as stainless steel and bearing steel. Sliding bearings must work under the protection of lubricating oil or grease, and must maintain a good fluid dynamic lubrication state during operation. With the rapid development of the aerospace and automotive industries, more stringent requirements have been put forward for titanium alloy sliding bearings in terms of accuracy, speed, life, reliability, temperature, etc. In high temperature environments, lubricating oil and grease are easily diluted and evaporated, resulting in a lack of lubrication conditions, resulting in boundary friction or even dry friction between the friction pairs, aggravating bearing wear, and causing the friction pairs to fail due to adhesive wear, abrasive wear, bonding, fatigue wear, etc., thereby limiting their service life and application areas.

[0003] In order to solve the above problems, many studies have been carried out in terms of material design and preparation process. For example, common strengthening phases with self-lubricating function such as graphene and Ti3SiC2 are directly added to titanium alloy powder for spark plasma sintering, and the friction coefficient can be reduced to 0.37 and the wear rate is 2.35×10 -4 mm 3 ·N -1 ·m -1 . Single-component self-lubricating materials only have good lubrication effects in limited and specific environments. By utilizing the synergistic lubrication effects of multiple lubricating phase components, good tribological properties of composite materials can be guaranteed in a wider temperature range. For example, when MoS2 and Pb multi-component materials with anti-friction functions are directly added to titanium alloys, composite lubricating films such as PbMoO4 and Pb can be formed, which have good self-lubricating properties. The above measures have improved the wear resistance of titanium alloy sliding bearings to a certain extent. However, the direct doping of solid self-lubricating phases in titanium alloys will lead to weak interface bonding between them, and the self-lubricating phases are prone to become the source of cracks during load friction. On the other hand, relying solely on self-lubricating phase materials to enhance the wear resistance of titanium alloy sliding bearings still shows the problem of insufficient wear resistance. Therefore, further improving the wear resistance of titanium alloy sliding bearings has become an important issue that needs to be solved urgently. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a friction-reducing and anti-wear titanium alloy for bearings with high wear resistance and strong lubricity.

[0005] Another object of the present invention is to provide a method for preparing a friction-reducing and anti-wear titanium alloy for bearings with high wear resistance and strong lubricity.

[0006] Technical solution: The anti-friction and anti-wear titanium alloy for bearings of the present invention comprises a matrix, the surface of which is loaded with Ti3AlC2, Mo2AlC2, and Ti3Al nanophases with self-lubricating function formed by in-situ reaction.

[0007] Preferably, the Ti3AlC2 and Mo3AlC2 phases are formed by high-temperature reaction of TiC, Mo2C and Al in the Ti-Al composite coating under the action of a high-energy femtosecond laser beam.

[0008] Preferably, the Ti3Al phase is formed by a high-temperature in-situ reaction of Ti and Al in the Ti-Al composite coating under the action of a high-energy femtosecond laser beam.

[0009] Preferably, the matrix is ​​one of Ti-Al, Ti-Sn, Ti-Zr, and Ti-Mo.

[0010] The method for preparing the friction-reducing and wear-resistant titanium alloy for bearings of the present invention comprises the following steps:

[0011] (1) TiCl4, AlCl3 and 1-ethyl-3-methylimidazole chloride are prepared into a mixed solution;

[0012] (2) adding nano-TiC and Mo2C particles to the mixed solution of step (1) and stirring;

[0013] (3) immersing the substrate in an HF solution for ultrasonic etching;

[0014] (4) adding 4-cyanopyridine and magnesium powder to the mixed solution obtained in step (2), and using an ionic liquid mixed electrodeposition process to deposit a titanium aluminum coating on the surface of the substrate corroded in step (3) to obtain a composite material;

[0015] (5) Scanning the composite material in step (4) with a high-energy femtosecond laser beam to form a microporous structure loaded with in-situ nano self-lubricating Ti3AlC2, Mo2AlC2 and Ti3Al particles on the coating surface.

[0016] Preferably, in the step (1), the molar ratio of TiCl4, AlCl3 and 1-ethyl-3-methylimidazole chloride is 1:2:1 to 1.8:2:1, and more preferably 1.8:2:1.

[0017] Preferably, the molar ratio of nano-TiC to Mo2C particles in step (2) is 1:1 to 2:1, more preferably 2:1.

[0018] Preferably, the substrate in step (3) is one of Ti-Al, Ti-Sn, Ti-Zr, and Ti-Mo, and more preferably Ti-Al.

[0019] Preferably, the concentration of 4-cyanopyridine in step (4) is 0.2-0.4 g / L, preferably 0.4 g / L.

[0020] Preferably, the concentration of magnesium powder in step (4) is 2-5 g / L, more preferably 2 g / L.

[0021] Preferably, the electrodeposition current density in step (4) is 10-40 mA / cm 2 , more preferably 10 mA / cm 2 .

[0022] Preferably, the electrodeposition temperature in step (4) is 20-50°C, more preferably 20°C.

[0023] Preferably, in step (5), the scanning power of the high-energy femtosecond laser beam is 0.5-1W.

[0024] Principle of the invention: Based on the excellent performance and interface characteristics of the self-lubricating phase generated by in-situ reaction, and in accordance with the principles of materials science, a titanium-aluminum composite coating with nano-TiC and Mo2C particles deposited on the surface of titanium alloy is designed. The high-temperature excitation of a high-energy femtosecond laser beam is used to induce in-situ reactions between Ti-Al-C, Mo-Al-C, and Ti-Al, forming a microporous structure loaded with in-situ nano-self-lubricating Ti3AlC2, Mo2AlC2, and Ti3Al particles with self-lubricating function. Among them, the nano-self-lubricating Ti3AlC2, Mo2AlC2 phases and Ti3Al particles act as solid self-lubricating components during the friction process, thereby reducing the wear rate. The microporous structure can store the lubricating medium and continuously release the lubricating medium during the friction process, thereby significantly reducing the wear rate of the titanium alloy sliding bearing under the synergistic effect of the lubricating multi-component phase and the microporous structure.

[0025] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0026] (1) This method uses an ionic liquid mixed electrodeposition process to electrodeposit a Ti-Al composite coating loaded with TiC and Mo2C on the surface of a titanium alloy. Based on the in-situ reaction principle, a high-energy femtosecond laser beam is scanned on the surface of the composite material to induce an in-situ reaction between Ti-Al-C, Mo-Al-C, and Ti-Al, forming nano-Ti3AlC2, Mo2AlC2 phases, and Ti3Al particle phases with self-lubricating functions, which can effectively reduce the wear rate of titanium alloy bearings.

[0027] (2) This method makes full use of the interaction between the femtosecond laser beam and the titanium alloy to form a microporous structure with in-situ nanophase loading. The microporous structure acts as a storage bin for the lubricating medium, continuously releasing the lubricating medium during the friction process, thereby significantly reducing the wear rate of the titanium alloy bearing. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a microstructure diagram of the titanium alloy obtained in Example 1;

[0029] Figure 2 It is a comparison chart of the friction coefficients of the titanium alloys obtained in Examples 1-4 and Comparative Examples 1-2;

[0030] Figure 3 It is a comparison chart of the wear rates of the titanium alloys prepared in Examples 1-4 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described below in conjunction with embodiments.

[0032] Example 1

[0033] The anti-friction and anti-wear titanium alloy for bearings described in the present invention comprises a substrate, the surface of the substrate is loaded with Ti3AlC2, Mo2AlC2, and Ti3Al nanophases with self-lubricating function formed by in-situ reaction; the Ti3AlC2 and Mo3AlC2 phases are formed by high-temperature reaction of TiC, Mo2C and Al in the Ti-Al composite coating under the action of a high-energy femtosecond laser beam; the Ti3Al phase is formed by high-temperature in-situ reaction of Ti and Al in the Ti-Al composite coating under the action of a high-energy femtosecond laser beam.

[0034] The method for preparing the friction-reducing and wear-resistant titanium alloy for bearings of the present invention comprises the following steps:

[0035] (1) taking TiCl4, AlCl3 and 1-ethyl-3-methylimidazole chloride in a molar ratio of 1:2:1 to form a mixed solution;

[0036] (2) adding nano-TiC and Mo2C particles in a molar ratio of 1:1 into the mixed solution of step (1) and performing ultrasonic dispersion and stirring;

[0037] (3) immersing the titanium alloy in a 1-2% HF solution and ultrasonically corroding it for 3-5 minutes;

[0038] (4) Add 0.2 g / L 4-cyanopyridine and 2 g / L magnesium powder to the mixed solution obtained in step (2), adopt an ionic liquid mixed electrodeposition process, use the surface corroded titanium alloy in step (3) as a cathode in an inert argon protection environment, graphite as an anode, and the electrodeposition current density is 10 mA / cm2 , the temperature is 20°C, and a titanium-aluminum coating containing nano-TiC and Mo2C particles is deposited on the surface of the titanium alloy;

[0039] (5) In an inert argon environment, a high-energy femtosecond laser beam with a scanning power of 0.5 W is used to scan the titanium-aluminum coating containing nano-TiC and Mo2C particles on the surface of the titanium alloy in step (4), and an in-situ reaction among Ti-Al-C, Mo-Al-C, and Ti-Al is induced at high temperature, thereby forming a microporous structure loaded with in-situ nano-self-lubricating Ti3AlC2, Mo2AlC2, and Ti3Al particles on the surface of the coating.

[0040] Under the conditions of 15N positive pressure, TC4 as friction pair and dry friction, the friction amplitude was 1mm for 60min to obtain the friction coefficient and wear rate of the titanium alloy. The wear rate was measured by a three-dimensional profiler to measure the three-dimensional profile of the wear scar, and then the wear volume was calculated.

[0041] Figure 1 1 is a microstructure diagram of the titanium alloy obtained in Example 1, wherein 1-Ti3AlC2, 2-Mo2AlC2, 3-Ti3Al. Figure 1 It can be found that nanoscale Ti3AlC2 and flaky Mo2AlC2 can be evenly distributed on the surface of the microporous structure, and the nearly spherical Ti3Al in-situ phase is also evenly distributed on the surface of the microporous structure. It can also be found that there are no obvious interface defects between the above three phases and the matrix, indicating that the in-situ phase has good interface bonding performance with the matrix.

[0042] Example 2

[0043] The difference between this embodiment and embodiment 1 is that the molar ratio of TiCl4, AlCl3 and 1-ethyl-3-methylimidazole chloride in step (1) is adjusted to 1.8:2:1.

[0044] Example 3

[0045] The difference between this embodiment and embodiment 2 is that in step (2), the molar ratio of nano-TiC to Mo2C particles is adjusted to 2:1.

[0046] Example 4

[0047] The difference between this embodiment and embodiment 3 is that the concentrations of 4-cyanopyridine and magnesium powder in step (4) are adjusted to 0.4 g / L and 5 g / L, respectively.

[0048] according to Figure 2It can be seen that the friction coefficients of the low-friction titanium alloys obtained in Examples 1-4 are all lower than 0.1, while in the prior art, the friction coefficient of the titanium alloy containing a textured surface and reinforced with molybdenum disulfide measured under dry friction conditions is 0.2 (Zhao Qiancheng, Cao Wenhui, Song Junjie, et al. Preparation of MoS2 film on textured titanium alloy surface and study of its micro-tribological properties [J]. Journal of Tribology (Chinese and English), 2024, 44(06): 842-853.), which is about twice the friction coefficient of the titanium alloy obtained in this scheme. This shows that under the synergistic effect of the in-situ synthesized multi-self-lubricating components, the friction coefficient of the titanium alloy is significantly reduced.

[0049] according to Figure 3 It can be seen that the wear rates of the titanium alloys with microporous structures loaded with in-situ nano-Ti3AlC2, Mo3AlC2, and Ti3Al lubricating phases prepared in Examples 1-4 are all lower than 1.2, while the wear rate of the titanium alloy with a single PTFE spray texture surface measured under dry friction conditions is about 1.6×10 -6 mm -3 ·N -1 ·m -1 (Ma Zhen, Cao Wenhui, Fan Hengzhong, et al. Preparation of self-lubricating composite wear-resistant structure on titanium alloy surface and study of its friction properties [J]. Journal of Tribology, 2022, 42(06): 1184-1195.), further illustrating that this method can effectively reduce the wear rate of titanium alloy sliding bearings.

[0050] Comparative Example 1

[0051] The similarities between this comparative example and Example 1 are not repeated here. The difference is that the titanium-aluminum composite coating is not deposited on the surface of the titanium alloy powder in steps (1), (2) and (3), and a high-energy femtosecond laser beam is directly used to scan and shape the titanium alloy surface.

[0052] Comparative Example 2

[0053] The similarities between this comparative example and Example 1 are not repeated here. The difference is that step (2) is not adopted, and only a titanium-aluminum coating is deposited on the surface of the titanium alloy powder, and a high-energy femtosecond laser beam is used to scan and shape the titanium alloy surface.

[0054] The titanium alloy prepared in Comparative Example 1 only contains surface microporous structures. Figure 2-3 It can be seen that its friction coefficient is significantly higher than the friction coefficient of the titanium alloy with microporous structure loaded with in-situ nano-Ti3AlC2, Mo3AlC2, and Ti3Al lubricating phases prepared by this method (about 2 to 5 times); the wear rate of the titanium alloy prepared in Comparative Example 1 is about 3 to 7 times the wear rate of the low-friction titanium alloy prepared by this method. The titanium alloy with microporous structure loaded with only Ti3Al nano-phase prepared in Comparative Example 2 has a friction coefficient and a wear rate of about 0.19 and 2.9×10-6 mm -3 ·N -1 ·m -1 It is shown that the in-situ doping of nano-Ti3AlC2, Mo3AlC2, and Ti3Al lubricating phases in the present application can give the titanium alloy a lubricating function in the friction process, reduce the degree of wear in the wear process, and thus improve the wear resistance of the sliding bearing. This further proves that the in-situ formation of multi-element self-lubricating phase doping in the present method can significantly improve the wear resistance of the titanium alloy sliding bearing.

Claims

1. A friction-reducing and wear-resistant titanium alloy for bearings, characterized in that: The invention comprises a matrix, and the surface of the matrix is ​​loaded with Ti3AlC2, Mo2AlC2, Ti3Al nano phases with self-lubricating function formed by in-situ reaction.

2. The anti-friction and anti-wear titanium alloy for bearings according to claim 1, characterized in that: The Ti3AlC2 and Mo3AlC2 phases are formed by high-temperature reaction of TiC, Mo2C and Al in the Ti-Al composite coating under the action of a high-energy femtosecond laser beam.

3. The anti-friction and anti-wear titanium alloy for bearings according to claim 1, characterized in that: The Ti3Al phase is formed by high-temperature in-situ reaction of Ti and Al in the Ti-Al composite coating under the action of a high-energy femtosecond laser beam.

4. The anti-friction and anti-wear titanium alloy for bearings according to claim 1, characterized in that: The matrix is ​​one of Ti-Al, Ti-Sn, Ti-Zr and Ti-Mo.

5. A method for preparing the anti-friction and anti-wear titanium alloy for bearings according to claim 1, characterized in that: The following steps are involved: (1) TiCl4, AlCl3 and 1-ethyl-3-methylimidazole chloride are prepared into a mixed solution; (2) adding nano-TiC and Mo2C particles to the mixed solution of step (1) and stirring; (3) immersing the substrate in an HF solution for ultrasonic etching; (4) adding 4-cyanopyridine and magnesium powder to the mixed solution obtained in step (2), and using an ionic liquid mixed electrodeposition process to deposit a titanium aluminum coating on the surface of the substrate corroded in step (3) to obtain a composite material; (5) Scanning the composite material in step (4) with a high-energy femtosecond laser beam to form a microporous structure loaded with in-situ nano self-lubricating Ti3AlC2, Mo2AlC2 and Ti3Al particles on the coating surface.

6. The preparation method according to claim 5, characterized in that: In the step (1), the molar ratio of TiCl4, AlCl3 and 1-ethyl-3-methylimidazole chloride is 1:2:1 to 1.8:2:

1.

7. The preparation method according to claim 5, characterized in that: In the step (2), the molar ratio of nano-TiC to Mo2C particles is 1:1 to 2:

1.

8. The preparation method according to claim 5, characterized in that: The substrate in step (3) is one of Ti-Al, Ti-Sn, Ti-Zr, and Ti-Mo.

9. The preparation method according to claim 5, characterized in that: In the step (4), the concentrations of 4-cyanopyridine and magnesium powder are 0.2-0.4 g / L and 2-5 g / L respectively; the electrodeposition current density is 10-40 mA / cm 2 , the temperature is 20~50℃.

10. The preparation method according to claim 5, characterized in that: In the step (5), the scanning power of the high-energy femtosecond laser beam is 0.5 to 1 W.